Developments in structural engineering. proceedings of the Forth Rail Bridge Centenary Conference, held on the 21-23 August 1990 at the Department of Civil Engineering, Heriot-Watt University, Riccarton, Edinburgh, Scotland, UK /: proceedings of the Forth Rail Bridge Centenary Conference, held on the 21-23 August 1990 at the Department of Civil Engineering, Heriot-Watt University, Riccarton, Edinburgh, Scotland, UK. Bridges and space structures : Volume 1, ([2014?]) - Unknown
No abstract available